Rockets and feathers revisited: An international comparison on European gasoline markets - Marzio Galeotti; Alessandro Lanza; Matteo Manera (Fondazione Eni Enrico Mattei (FEEM), 2002)
This paper re-examines the issue of asymmetries in the transmission of shocks to crude oil prices onto the retail price of gasoline. Relative to the previous literature, the distinguishing features of the present paper are: i) use of updated and comparable data to carry out an international comparison of gasoline markets; ii) two-stage modeling of the transmission of oil price shocks to gasoline prices (first refinery stage and second distribution stage), in order to assess possible asymmetries at either one or both stages; iii) use of asymmetric error correction models to distinguish between asymmetries that arise from short-run deviations in input prices and from the speed at which the gasoline price reverts to its long-run level; iv) explicit, possibly asymmetric, role of the exchange rate, as crude oil is paid for in dollars whereas gasoline sells for different sums of national currencies; v) bootstrapping of F tests of asymmetries, in order to overcome the low-power problem of conventional testing procedures. In contrast to several previous findings, the results generally point to widespread differences in both adjustment speeds and short-run responses when input prices rise or fall.
Keywords: C22; D40; Q40; 330; Gasoline prices; speed of adjustment; asymmetric adjustment; exchange rate; Ölpreis; Ölpreis; Benzin; Tankstelle; Anpassung; Vergleich; Industriestaaten